2022
DOI: 10.1371/journal.pone.0270920
|View full text |Cite
|
Sign up to set email alerts
|

ACE2-like enzyme B38-CAP suppresses abdominal sepsis and severe acute lung injury

Abstract: Angiotensin-converting enzyme 2 (ACE2) is the carboxypeptidase to degrade angiotensin II (Ang II) to angiotensin 1–7 (Ang 1–7) and improves the pathologies of cardiovascular disease and acute respiratory distress syndrome (ARDS)/acute lung injury. B38-CAP is a bacteria-derived ACE2-like carboxypeptidase as potent as human ACE2 and ameliorates hypertension, heart failure and SARS-CoV-2-induced lung injury in mice. Recombinant B38-CAP is prepared with E. coli protein expression system more efficiently than recom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Puncturing the cecum, which contains bacteria, leads to bacterial peritonitis and the translocation of bacteria into the bloodstream, ultimately resulting in septic shock. CLP mice exhibit high mortality and histopathological changes associated with ARDS, including the destruction of the alveolar structure, thickening of the pulmonary septa, hemorrhaged lung tissue, and the infiltration of inflammatory cells [40,41].…”
Section: Clp-induced Sepsis Modelmentioning
confidence: 99%
“…Puncturing the cecum, which contains bacteria, leads to bacterial peritonitis and the translocation of bacteria into the bloodstream, ultimately resulting in septic shock. CLP mice exhibit high mortality and histopathological changes associated with ARDS, including the destruction of the alveolar structure, thickening of the pulmonary septa, hemorrhaged lung tissue, and the infiltration of inflammatory cells [40,41].…”
Section: Clp-induced Sepsis Modelmentioning
confidence: 99%
“…Another potential mechanism might BE related to the effect of PCSK9 on angiotensin-converting enzyme 2 (ACE2) entry receptors in COVID-19 [8]. Likewise, it has been reported that ACE2 suppresses abdominal sepsis and severe acute lung injury [9]. It is known that PCSK9 enhances the degradation of ACE2 which is anti-inflammatory by requiring different domains that those critical for the LDL receptor degradation by PCSK9.…”
Section: Putative Mechanisms Of Pcsk9-induced Inflammation In Sepsismentioning
confidence: 99%
“…B38-CAP, an ACE2-like enzyme derived from Bacillus-like bacteria, can upregulate the level of angiotensin 1–7, reduce the levels of Ang II and inflammatory cytokines and chemokines, improve lung injury caused by sepsis, and increase the survival rate of CLP mice by 20% [ 48 ].…”
Section: Proteins and Peptidesmentioning
confidence: 99%